Quality of life and disability : an approach for community practitioners - Brown, Ivan, 1947- (Jessica Kingsley, 2003)
Quality of life - physical, psychological and environmental well-being - is a crucial consideration for professionals working with people with a disability. The authors of this practical book apply ideas about quality of life to the field of disability to assist front-line professionals, managers and policy-makers in effective service provision. They examine the historical context of the concept of quality of life, and discuss the application of quality of life in the daily lives of people who are disabled. Using recent studies to show how the development of quality of life models have led to.